Postoperative outcomes of ureteroscopy for pediatric urolithiasis: A secondary analysis of the National Surgical Quality Improvement Program Pediatric. Issue 5 (October 2021) - Davidson, Jacob; Ding, Youshan; Chan, Ernest; Dave, Sumit; Bjazevic, Jennifer; Filler, Guido; Wang, Peter Zhan Tao
Summary: Introduction: Incidence of pediatric urinary stone disease (PUSD) has increased over recent decades. Innovations in ureteroscopic technology has expanded the role of endourologic stone management in children. However, there is currently no consensus on the optimal use of ureteroscopy (URS) within the heterogenous PUSD population. Objective: The primary objective was to investigate the rate of 30-day unplanned readmissions in pediatric patients after URS. The secondary objective was to examine the influence of demographic, perioperative, postoperative, and reoperation variables as predictors of an increased risk of unplanned readmission in this sample. Study design: A secondary analysis was performed on retrospectively collected data from the National Surgical Quality Improvement Program Pediatric between 2015 and 2018. Pediatric patients diagnosed with PUSD and treated with URS were identified. Patients undergoing concurrent or additional surgeries during the URS procedure were excluded. Data on demographic, perioperative, postoperative, and unplanned reoperation variables were examined for their possible influence on 30-day unplanned readmissions. Descriptive statistics were used to characterize the study cohort. Continuous and categorical variables were analyzed using independent samples t-test, one-way ANOVA with Tukey post-hoc test, and Chi-square Tests or Fisher's Exact Test, respectfully. Multivariate analysis was performed using stepwise logistic regression. Results: A total of 2510 patients were identified within the study period. The majority of children undergoing URS were between 12 and 18 years of age (66.1%), female (56.9%), and had renal calculi (45.2%). Of these, 162 (6.5%) experienced a 30-day unplanned readmission related to the URS procedure. The most common reasons for an unplanned readmission was urinary tract infection (31.4%), new/unresolved stone (28.3%), and postoperative pain (8.2%). Multivariate modelling showed that females (Relative Risk [RR]: 2.03; 95% Confidence Interval [95%CI]: 1.34–3.07), patients with renal stones (RR: 1.77; 95%CI: 1.10–2.83), and inpatients at the time of surgery (RR: 1.61; 95%CI: 1.03–2.51) were more at risk of an unplanned readmission within 30-days of an URS procedure. Summary Table Multivariate analysis of patient variables associated with 30-day unplanned readmission following ureteroscopy Summary Table   Relative Risk (95% CI) Sex  Male Ref.  Female 2.03 (1.34–3.07) Stone location  Renal 1.77 (1.10–2.83)  Both ureteric and renal stone 1.29 (0.74–2.25)  Ureteric Ref. Previous Cardiac Surgery  Yes 6.60 (2.55–17.08)  No Ref. Patient status at time of surgery  Inpatient 1.61 (1.03–2.51)  Outpatient Ref. 1 The following variables were also included in the multivariate model, but were not statistically significant: age group, weight quartile, ureteral stent, American Society of Anesthesiologists (ASA) class, case type, previous cardiac surgery, and premature birth. Conclusion: This study reports on short-term unplanned readmission rates in pediatric patients who underwent an URS procedure. Further it highlights possible predictors of unplanned readmission rates within a sampling of patients from NSQIP affiliated institutions. The findings from this study can be used to guide future studies around the safe use of URS in pediatric patients.